2021
DOI: 10.1002/ps.6282
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and physiological responses of Drosophila melanogaster and D. suzukii to volatiles from plant essential oils

Abstract: BACKGROUND Insects rely on their sense of smell to locate food and hosts, find mates and select sites for laying eggs. Use of volatile compounds, such as essential oils (EOs), to repel insect pests and disrupt their olfaction‐driven behaviors has great practical significance in integrated pest management. However, our knowledge on the olfaction‐based mechanisms of EO repellency is quite limited. RESULTS We evaluated the repellency of peppermint oil and nine plant EO components in Drosophila melanogaster, a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Gomez-Diaz, Martin, Garcia-Fernandez, and Alcorta [ 58 ], Leal [ 60 ] described that the insect sensilla comprises pores in the cuticle that allow odorants to diffuse into the nerve system. The located ORs are also described as odour-specific, especially natural products such as essential oils [ 61 , 62 ]. In the ORF, in particular, its ORs are able to bind structurally with all portions of methyl eugenol molecule and respond to ortho-substituted benzenes with adjacent oxygen atoms or isoelectronic equivalents [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gomez-Diaz, Martin, Garcia-Fernandez, and Alcorta [ 58 ], Leal [ 60 ] described that the insect sensilla comprises pores in the cuticle that allow odorants to diffuse into the nerve system. The located ORs are also described as odour-specific, especially natural products such as essential oils [ 61 , 62 ]. In the ORF, in particular, its ORs are able to bind structurally with all portions of methyl eugenol molecule and respond to ortho-substituted benzenes with adjacent oxygen atoms or isoelectronic equivalents [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant volatiles can act as important chemical signals that form communication links between insect herbivores and their host plants and function as either attractants or repellents [15,16]. In this study, we investigated which peanut volatile components play a role in host plant selection in H. parallela.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethrum also repelled D. suzukii in these assays (S1 Fig). Furthermore, we performed the two-choice assay in the presence of an attractant, apple cider vinegar (ACV), i.e., a two-choice attraction assay [24] (S1 Fig) and found that both D. melanogaster and D. suzukii were repelled by pyrethrum in this assay as well (S1 Fig).…”
Section: Pyrethrum Repels D Melanogaster and D Suzukiimentioning
confidence: 99%
“…Single sensillum recording was conducted with electrolytically sharpened tungsten microelectrodes as previously described [13,24,31]. A 0.1 mm diameter tungsten wire was sharpened by repeatedly dipping its tip in a 10% KNO 2 solution electrified at 5-10 mV.…”
Section: Single Sensillum Recording (Ssr)mentioning
confidence: 99%